Surface patterns of reactive species on model tissue treated by a surface air discharge. (12th March 2019) - He, Tongtong; Liu, Dingxin; Wang, Bingchuan; Wang, Weitao; Liu, Zhichao; Guo, Li; Rong, Mingzhe; Kong, Michael G
Abstract: Surface dielectric barrier discharge is capable of generating large-scale, flexible-shape and chemically active plasmas in open air, and hence has attracted much attention with relevance to clinical applications. An important application requirement is that the plasma treatment should have good homogeneity, which can be reflected by the surface distributions of reactive species on the treated sample. In this letter, a surface air discharge was used to treat a model tissue made of gelatin gel, and the surface distributions of H +, and O3 were detected. When the air gap width between the plasma and the model tissue is 3 mm, it is found that the distributions have mesh patterns similar to that of the ground electrode, but O3 concentrates on the edges of each mesh element, while and H + concentrate in the center part. A wider air gap width benefits the mixing of reactive species but their surface distributions are more inhomogeneous, which should ascribe to a weak gas flow caused by the ionic wind and/or the gas heating effect. Gas flow can also be generated by rotating the plasma source, which is found to achieve a good homogeneity of treatment with a slow rotating speed of 1.2–2.4 rpm. This approach is easy to implement in clinical applications.